MOTIVASI PENGUNJUNG PADA DESTINASI WISATA EDUKASI PERPUSTAKAAN SOEMAN HS KOTA PEKANBARU PROVINSI RIAU - Febrian, Rizki; Sidiq, Rd. Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
The Soeman HS Library recorded a significantly higher visitation rate than other educational tourism destinations in Pekanbaru City, with 219,316 visitors in 2024. This high visitation phenomenon occurs amidst the ease of digital literacy access, indicating a transformation in visitor preferences from mere conventional book lending toward seeking direct physical experiences. This study aims to analyze the educational tourism motivation factors that primarily drive visitors' decisions to visit the Soeman HS Library in person. The method used was quantitative descriptive, involving 100 respondents selected via simple random sampling techniques. Data analysis was performed using descriptive statistics to measure mean values across five motivational dimensions. The results indicate that Physical Motivation is the primary driving factor with the highest score (4.38), followed by Fantasy Motivation (4.22). These findings confirm that visitors' main priorities are seeking a new atmosphere (refreshment) and escaping from daily routine boredom (escapism). Meanwhile, Spiritual Motivation (4.03) and Social Motivation (3.87) were also classified as high, reflecting needs for silence and interaction spaces. Conversely, Cultural Motivation recorded the lowest score (3.70), suggesting that interest in history remains below the visual appeal of architecture. It is concluded that a shift in dominant motivation has occurred from pure literacy needs toward recreational aspects, therefore recommending interactive cultural collection innovations and physical facility maintenance to sustain visitation. Keyword: Soeman HS Library, Educational Tourism, Visitor Motivation,